Exploring and Leveraging Chinese International Students’ Strengths for Success - He, Ye; Hutson, Bryant (Journal of International Students, 2018)
This study used an Appreciative Education framework to explore the strengths of Chinese international students and to identify areas where support is needed during their transition to U.S. higher education settings. Using a convergent mixed methods design with data collected from surveys, interviews and focus groups, the complex nature of the transition process was explored. While commitment and motivation, as well as familial support, were identified as strengths based on survey data, interview and focus group data revealed additional strengths and how students leverage these strengths to support their transition. The findings led to insights and recommendations for higher education professionals working with Chinese international students specifically and offered approaches to better understand and support international students in general.